Development of School Level Assessment Tools (SLATs) to fix Student's Learning Levels (SSLs) in Linguistic Skills and Numeric Abilities with Guidelines for Pedagogy at Primary Stage - Somasundharam, D. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Aim - To fix the learning level of the students at Primary stage based on Learning Indicators (LINDICS)/ Learning Outcomes. Taking sample of students studying V-std and assess the learning level of students in Literacy skills (both Tamil & English) and Numeric abilities (Mathematics). Title - “Development of School Level Assessment Tools (SLATs) to fix Student's Learning Levels(SLLs) in Linguistic Skills & Numeric Abilities with Guidelines for Pedagogy at Primary Stage” Towards effective and productive learning, the primary aim is to focus on the learning outcomes to be developed among the students at the end of each grade. Finding their attainment in learning outcomes is a challenging one at school level. Every teacher must know their student's level at the beginning as well as at the end of each academic year for their achievement. This leads to monitor the progressive nature of students in his/ her classroom climate. SLLs Assessment is a tool here to fix the learning levels of students in Language skills and Mathematical abilities at primary stage. Every teacher in the education system has to be taken this School Level Assessment Tool (SLAT) as a weapon to evaluate their students learning outcomes, whenever required.